MOTIVASI RUSIA MERATIFIKASI PARIS AGREEMENT PADA TAHUN 2019 - Marsaulina Siahaan; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The Paris Agreement is an agreement that focuses on enhancing the global response to climate change. Russia as one of the countries that ratified the agreement. This study aims to determine Russia's motivation in ratifying the Paris Agreement in 2019. This research implies qualitative method with explanative research type. In analyzing this phenomenon, this research implies the Foreign Policy Theory by Graham T. Allison in the perspective of Realism, state is the level analysis in this researched. To analyze this research, the authors collect documents and information from books, journals, websites and various official websites. Based on the analysis carried out, it is shows that Russia's policy motivation in ratifying the Paris Agreement is influenced by several things, in accordance with this research hypothesis that Russia's ratification of the Paris Agreement is to prove that the Russia is an essential actor in international politics, took action against the Paris agreement as an opportunity to improve its international image. Keywords : Rusia, Foreign Policy Theory, Paris Agreement, essential actor